2023
DOI: 10.1107/s1600576723002674
|View full text |Cite
|
Sign up to set email alerts
|

101 contact twins in gypsum experimentally obtained from calcium carbonate enriched solutions: mineralogical implications for natural gypsum deposits

Abstract: Gypsum twins are frequently observed in nature, triggered by a wide array of impurities that are present in their depositional environments and that may exert a critical role in the selection of different twin laws. Identifying the impurities able to promote the selection of specific twin laws has relevance for geological studies aimed at interpreting the gypsum depositional environments in ancient and modern deposits. Here, the effect of calcium carbonate (CaCO3) on gypsum (CaSO4·2H2O) growth morphology has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(14 citation statements)
references
References 53 publications
(48 reference statements)
0
14
0
Order By: Relevance
“…In the range 1.97 < AR < 2.51, the aspect ratio of both 100 and 101 penetration twinning laws are measured and thus this range does not allow to distinguish between the two. Therefore, the AR parameter might be a fast and useful tool to distinguish between 100 and 101 penetration twins, in addition to those already described in Cotellucci et al 31 The curved habit of gypsum, also known as "bent habit", has already been reported in the literature. 34,35 To our knowledge, two different experimental growth conditions can promote the curvature in gypsum crystals: diffusion-controlled experiments in the presence of impurities, and evaporation experiments in the presence of impurities.…”
Section: Effect Of Different Evaporation Rates On Gypsummentioning
confidence: 79%
See 4 more Smart Citations
“…In the range 1.97 < AR < 2.51, the aspect ratio of both 100 and 101 penetration twinning laws are measured and thus this range does not allow to distinguish between the two. Therefore, the AR parameter might be a fast and useful tool to distinguish between 100 and 101 penetration twins, in addition to those already described in Cotellucci et al 31 The curved habit of gypsum, also known as "bent habit", has already been reported in the literature. 34,35 To our knowledge, two different experimental growth conditions can promote the curvature in gypsum crystals: diffusion-controlled experiments in the presence of impurities, and evaporation experiments in the presence of impurities.…”
Section: Effect Of Different Evaporation Rates On Gypsummentioning
confidence: 79%
“…We propose that 100 and 01 penetration twins have been observed in nature but inappropriately defined as “swallowtail twins”, which is the terminology commonly used to identify gypsum twinned crystals with a shape similar at first glance similar. Recently, straightforward and reliable methods have been proposed to geometrically and univocally recognize the different twinning laws of gypsum . Therefore, we strongly suggest improving the identification of the different gypsum twinning laws observed in nature, as they can serve as a proxy for the chemistry of the original water from which gypsum precipitated, , hence contributing to the interpretation of the gypsum depositional environment in ancient deposits.…”
Section: Results and Discussionmentioning
confidence: 97%
See 3 more Smart Citations